A Case for Gastrointestinal Specific Polyps in Neurofibromatosis Type I - Jonathan Rozenberg; Adil Mir; Klaus Mönkemüller; Bara El Kurdi; Douglas Grider (Gastro Hep Advances)
Neurofibromatosis type I (NF-1) is a common, autosomal dominant tumor syndrome whose diagnostic criteria consists of neuro-ophthalmologic, dermatologic, and/or osseous findings with concomitant genetic testing. Gastrointestinal manifestations are identified in 11%–25% of patients, yet these findings are not included in said criteria despite the growing evidence of specific gastrointestinal lesions in NF-1. We report a case of both ileal juvenile-like (inflammatory and hyperplastic) mucosal polyps and inflammatory fibroid polyps in an NF-1 patient.